1999
DOI: 10.1161/01.atv.19.10.2330
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Coculture Model of Transmigrant Monocytes and Foam Cell Formation

Abstract: Abstract-To analyze in vitro the migration of monocytes to the subendothelial space, their differentiation into macrophages, and the subsequent formation of foam cells in vitro, we have developed a 2-coculture system with rabbit aortic endothelial cells (AECs), aortic smooth muscle cells (SMCs), and a mixture of matrix proteins on polyethylene filters in chemotaxis chambers. AECs were seeded on a mixture of type I and IV collagen with or without various types of serum lipoproteins (method 1) or on matrix prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 40 publications
1
36
1
1
Order By: Relevance
“…Also, it has been reported that in certain subtypes, THP-1 cells do not express scaven-ger receptor activity upon PMA treatment (7). Furthermore, the induction of the liver x receptor alpha (LXRα) gene is not observed in THP1PMA cells, in contrast to our previous reported finding of the induction of this important receptor gene in macrophages (8). We studied the gene expression profile of THP1PMA cells and compared it with the expression profile of macrophages by means of oligonucleotide microarray analysis.…”
Section: Introductioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Also, it has been reported that in certain subtypes, THP-1 cells do not express scaven-ger receptor activity upon PMA treatment (7). Furthermore, the induction of the liver x receptor alpha (LXRα) gene is not observed in THP1PMA cells, in contrast to our previous reported finding of the induction of this important receptor gene in macrophages (8). We studied the gene expression profile of THP1PMA cells and compared it with the expression profile of macrophages by means of oligonucleotide microarray analysis.…”
Section: Introductioncontrasting
confidence: 95%
“…To differentiate THP-1 cells, PMA (SIGMA) was added to a final concentration of 0.2 µm and cultured for 72 hours or 7 days. Peripheral blood monocyte cells (PBMC) were isolated from normal human healthy volunteers and enriched by centrifugation with Ficoll-Paque Plus (Pharmacia Biotech, Uppsala, Sweden), and then were separated using magnetic beads conjugated with anti-human CD14 antibody as described previously (8). Some of them were immediately used for microarray analysis.…”
Section: Cell Culture and Pma Induced Differentiationmentioning
confidence: 99%
“…Oxidative modification of low density lipoprotein and successive uptake by macrophages leads to foam cell formation, which is a key cellular event during atherogenesis (5). During atherogenesis, monocytes transmigrate into vessel walls where they differentiate into macrophages and take up modified lipoproteins (6). During the course of the analysis of gene expression profile of monocyte/macrophage, we found that LXRa is profoundly induced in macrophages differentiated in the presence of GM-CSF.…”
Section: Introductionmentioning
confidence: 83%
“…Rabbit aortic SMCs and ECs were cocultured as described (28). Briefly, 1 × 10 6 rabbit aortic SMCs were cultivated with EGM-2 media (containing 2% rabbit plasma) on the filter for more than 3 weeks.…”
Section: Cats -/-Ldlr -/-Mouse Generation and Animal Protocolmentioning
confidence: 99%